Update From the Advisory Committee on Immunization Practices. (18th November 2016) - Schuster, Jennifer E.; O'Leary, Sean; Kimberlin, David W.
Abstract: The Advisory Committee on Immunization Practices (ACIP) consists of medical and public health experts who develop recommendations on vaccine use in the United States. The ACIP meets 3 times per year, and members and Centers for Disease Control (CDC) staff present findings and discuss vaccine research, vaccine effectiveness (VE) and safety, clinical trial results, and labeling/package insert information. Outbreaks of vaccine-preventable diseases and vaccine shortages are also discussed. Nonvoting representatives from the American Academy of Pediatrics and the Pediatric Infectious Diseases Society are present. The ACIP met on June 22–23, 2016 to discuss proposed recommendations for influenza vaccination, for human papillomavirus (HPV) vaccine dosing schedules, for the cholera vaccine (CVD 103-HgR), and for the use of MenACWY in human immunodeficiency virus (HIV)-infected persons, as well as an overview of respiratory syncytial virus (RSV) vaccines, safety of maternal tetanus, diphtheria, acellular pertussis (Tdap) immunization, and laboratory containment of poliovirus type 2.